Too Small to Fail? : Subnational Spending Pressures in Europe - Eyraud, Luc (IMF Working Papers; Working Paper, 2013)
The purpose of this paper is to assess whether expenditure decentralization has contributed to weakening fiscal performance in Europe. Using a panel of EU15 countries for the period 1995-2011, we estimate three econometric models and ask the following questions: (1) does the form of spending decentralization affect the general government fiscal balance?; (2) is there evidence of spending duplication?; and (3) are soft budget constraints prevalent at the subnational level in Europe? Our results indicate that current decentralization models may have some shortcomings and efforts to achieve fiscal consolidation would require improvements in three areas: better matching subnational spending and revenues; reshaping some expenditure assignments to reduce overlap; and improving the effectiveness of institutional arrangements at the subnational level.